Provision and cost of children's and young people's eye services in the UK: findings from a single primary care trust. Issue 5 (19th December 2008) - Alexander, P; Rahi, J S; Hingorani, M
Abstract : Aims/background: Population-based information is useful for future strategic planning of healthcare resources. We wished to describe and cost the provision of eye services, beyond those of basic primary and emergency care, for the paediatric population of a single primary care trust. Methods: Data from healthcare purchaser and provider records were collected for the year 2004/5 on provision and costing of hospital eye services, provision of spectacle vouchers, orthoptic screening, social services and visual-impairment team services to children in the Huntingdonshire Primary Care Trust population. Results: In the year of study, in a population of 33 564 aged under 18 years, 1870 (5.6%) children underwent screening by an orthoptist. 1970 (5.9%) children required outpatient appointments, 445 (1.3%) were prescribed spectacles, and 87 (0.3%) children needed surgical procedures. A small proportion (69, 0.2%) of children were visually impaired. The total cost of providing comprehensive eye services to children within Hunts PCT was £366 727. Conclusion: Although the prevalence of significant visual impairment is low in childhood, overall, eye conditions are common in children and may have lifelong implications. The resources required to provide a comprehensive paediatric eye service, to screen for and manage common eye conditions, and support those with serious eye conditions or visual impairment, are significant. This study aids quantified prediction of future service usage, and facilitates decision-making on resource allocation and workforce organisation for children's eye care in the UK.